Pengembangan Media Learning with Music untuk Meningkatkan Keterampilan Menulis Puisi pada Siswa Kelas X MAN 3 Langkat T.P 2022/2023 - Sulistiawati, Novi; Amaluddin, Amaluddin (Medan Resource Center, 2024)
This study aims to explore the development, feasibility, and effectiveness of Learning With Music Media for Poetry Text Material in Class X High School. Following the ADDIE developer model, the study progresses through research, data collection, design, product development, implementation, and evaluation. The population consists of 318 students, with a sample of 33 students. The developed product received a